Nilai Budaya Memoderasi Pengaruh Sistem Pengendalian Intern terhadap Penanggulangan Fraud dalam Pengelolaan Pajak Hotel di Kota Parepare - Hernianti Harun; Tenriwaru Tenriwaru; Julianty Sidik Tjan (Akuisisi: Jurnal Akuntansi, 2021)
This study aims: 1) To examine and analyze the internal control system that influences the prevention of fraud in hotel tax management in the city of Parepare. 2) To examine and analyze the cultural value of moderating the influence of the internal control system on fraud prevention in hotel tax management in the city of Parepare.This research was conducted in Parepare City from February to July 2021. The population in this study was 88 hotel entrepreneurs. Sampling using the census technique. The data analysis technique used the stimulus equation with the path analysis estimation technique. The application program Statistical Package for the Social Sciences (SPSS) version 23 was used to assist in analyzing the data used in this study. Using moderated regression analysis and Hypothesis Testing.The results of the study show that: 1) The internal control system has a significant effect on overcoming fraud in hotel tax management in the city of Parepare, because the implementation of the control system creates a supervisory system and internal procedures for each hotel in order to close all loopholes for fraud or financial abuse, including the payment of hotel taxes. 2) Cultural values moderate the influence of the internal control system on fraud prevention in hotel tax management in the city of Parepare. This means that the application of Bugis cultural values, including sipakatau', sipakalebbi and sipakalebbi, is able to strengthen the implementation of the internal control system at each hotel in the City of Parepare in relation to preventing fraud in hotel tax management.